PENGARUH POSITIVE REINFORCEMENT TERHADAP HASIL BELAJAR SEJARAH SISWA DI SMA ADIGUNA BANDAR LAMPUNG - Kurniawan, Putut Wisnu (STKIP PGRI Bandar Lampung, 2018)
The main problem in the history learning process seen in grade X students of Adiguna High School Bandar Lampung shows that the learning strategy used has not improved the students' learning motivation. The purpose of this study is to determine the influence of positive reinforcement on the learning outcomes of Adiguna high school students in Bandar Lampung lesson year 2017/2018. In the implementation of this study the authors use experimental methods, with a sample of 37. Sampling technique in this study using cluster random sampling technique, data collection techniques using the test. To test the hypothesis, the authors in this study using the formula ttes. From the research results obtained thit value = 4.45> ttab = 2,00 means it can be concluded